TINJAUAN LITERATUR TENTANG APLIKASI MOBILE DALAM MANAJEMEN KEUANGAN PRIBADI: Studi Platform dan Fitur Unggulan Aplikasi Keuangan Berbasis Mobile - Asyla Istah Nuresqi; Huda, Sheila Nurul (Lembaga Dongan Dosen, 2025)
Mobile applications have become an essential part of daily life, including personal financial management. This literature review investigates the roles and impacts of mobile applications in helping individuals manage their finances. The study highlights the use of Android-based personal finance applications. Additionally, hybrid mobile financial applications and digital imaging technology offer creative approaches t financial management. This study also discusses popular platforms and features, such as transaction recording, financial reporting, and dashboards. The findings indicate that mobile applications can enhance financial literacy and provide effective solutions for individuals to manage their finances effectively. This research is expected to serve as a reference for developers, academics, and policymakers in understanding trends in personal finance applications.